An improved Amplex Red‐based fluorometric assay of phenol oxidases and peroxidases activity: A case study on Haplic Chernozem. (15th March 2022) - Khosrozadeh, Sajedeh; Dorodnikov, Maxim; Reitz, Thomas; Blagodatskaya, Evgenia
Abstract: The initial steps of complex organic matter degradation in soil comprise several oxidative processes catalysed by phenol oxidases and peroxidases. Commonly, their activity is determined by colorimetric approaches based on a range of substrates, making comparison between studies difficult. To improve this shortcoming, we conducted a calibration procedure for assessing phenol oxidase and peroxidase activities in soils by a sensitive fluorometric assay. This assay is based on the colourless and non‐fluorescent Amplex Red® reagent as a substrate, which forms a fluorescent product, resorufin, upon oxidation. Commercially available resorufin was used as a standard for calibration. We applied Michaelis–Menten kinetics to determine functional traits of phenol oxidases and peroxidases in a case study on Haplic Chernozem from different land‐use and climate treatments of a field experiment. The kinetic parameters, limit of detection and limit of quantification demonstrated a high sensitivity of the fluorometric assay to differences caused by these treatments. For the total oxidative enzymes, the catalytic efficiency ( K cat, calculated as V max /K m ) was 30% higher in the cropland compared with the pasture plot. However, compared with soil samples collected from ambient climatic conditions, K cat of total oxidoreductases was 60% lower in cropland exposed to elevated air temperature and drought. The phenol oxidase activity was substantially higher than peroxidase activity in cropland land use. However, higher K cat of peroxidase than phenol oxidase resulted in 60% faster substrate turnover under both climatic conditions. In our case study, the Amplex Red‐based assay enabled rapid and high‐throughput analyses of phenol oxidase and peroxidase activity in soil. The sensitivity of this assay for soil enzymology applications needs further testing for a larger range of soils and environmental conditions. Highlights: A novel fluorometric assay of phenol oxidase and peroxidase activity in soil is proposed Resorufin fits very well for calibration simplifying the comparisons between studies Phenol oxidase and peroxidase displayed apparent Michaelis–Menten kinetics Amplex Red was sensitive for land‐use and climate treatments on Haplic Chernozem